Dynamic of Change in Soil Physical Properties and SoyBean Growth through The Application of Biochar on Lombok Vertisols - Sukartono; Rika Andrianti Sukma Dewi; Arifin Aria Bakti; Bambang Hari Kusumo (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Vertisol is a type of soil whose mineral fraction is dominated by 2:1 type clay minerals (smectite) which have the property of swelling-shrinking periodically as the soil water content changes. However, these physical properties can be improved by the application of biochar so that it can support plant growth. The aim of this study was to evaluate the effect of biochar on changes in the physical characteristics of vertisols soils and growth performance of soybean plants. This research was conducted in Kawo Village, Pujut District, Central Lombok. This study was designed to test the application of two types of biochar, namely rice husk biochar (BS) and corn cob biochar (BJ) at several doses, namely 0, 15, 30 and 60 g/kg of vertisols soil and design using a randomized block design with 6 replications. The parameters measured were unit weight, soil density, porosity, soil tensile strength, available water capacity, aggregate stability, cole value, crack pattern and soybean growth test. The results showed that the application of biochar could improve the physical properties of vertisol soil and also has implications for improving the growth of soybean plants. Observational data showed that a dose of 60 g/kg of biochar, both rice husk and corn cob biochar, showed better changes in soil physical properties compared to biochar doses of 15 g/kg, 30 g/kg and without the addition of biochar. Besides that, the treatment of rice husk and corn cob biochar at a dose of 60 g/kg gave better vegetative growth of soybean plants.